2013
DOI: 10.1017/s0950268813001866
|View full text |Cite
|
Sign up to set email alerts
|

Simulations to compare efficacies of tetravalent dengue vaccines and mosquito vector control

Abstract: SUMMARYInfection with dengue, the most prevalent mosquito-borne virus, manifests as dengue fever (DF) or the more fatal dengue haemorrhagic fever (DHF). DHF occurs mainly when an individual who has acquired antibodies to one serotype is inoculated with another serotype. It was reported that mosquito control may have increased the incidence of DF and DHF due to age-dependency in manifesting these illnesses or an immunological mechanism. Tetravalent dengue vaccine is currently being tested in clinical trials. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…14 In the context of giving examples on the situation of dengue prevention strategies in other regions, dengue vaccination has been confirmed to be the most cost-effective strategy in reducing the number of dengue cases, specifically in countries with a high number of cases and extensive vaccination coverage. 15 Many studies on dengue vaccine, including the specific vaccine type, mode of action, immune response, and vaccine effectiveness, confirmed promising results in reducing the number of dengue infection cases. 16e18 A preliminary clinical trial study, which took into account the correlation between the vaccine use with its impact on reducing the disease severity and viral transmission, confirmed a significant number of prevented infection cases.…”
Section: Introductionmentioning
confidence: 96%
“…14 In the context of giving examples on the situation of dengue prevention strategies in other regions, dengue vaccination has been confirmed to be the most cost-effective strategy in reducing the number of dengue cases, specifically in countries with a high number of cases and extensive vaccination coverage. 15 Many studies on dengue vaccine, including the specific vaccine type, mode of action, immune response, and vaccine effectiveness, confirmed promising results in reducing the number of dengue infection cases. 16e18 A preliminary clinical trial study, which took into account the correlation between the vaccine use with its impact on reducing the disease severity and viral transmission, confirmed a significant number of prevented infection cases.…”
Section: Introductionmentioning
confidence: 96%
“…There have been previous studies that have estimated the economic impact of dengue vaccines in Asia and South America, including Thailand, Argentina, and Brazil [2024], however, to our knowledge, ours is the first analysis of the cost-effectiveness of a dengue vaccination in Mexico with consideration of ADE. Whereas previous modeling studies have investigated the epidemiological effects of vaccine-induced ADE on dengue spread [25–28], its impact on the cost-effectiveness of dengue vaccination in Mexico remains unknown. In prior analyses, it was indicated that the epidemiological impact of the vaccine depends strongly on the local transmission intensity and the degree of vaccine-induced ADE, which could result in hospitalization for individuals who are vaccinated when they are seronegative and contract dengue disease thereafter [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the term “disease” is also valid for chronic and lifestyle diseases. Secondly, we needed to include general terms such as “transmi*” or “epidem*” to capture papers only describing their specific disease topic like influenza [ 69 ] or dengue [ 70 ]. Unfortunately, “transmi*” caused many false positive hits for research on power markets, sensors and information networks.…”
Section: Resultsmentioning
confidence: 99%